Pengaruh Religiusitas, Islamic Financial Literacy Serta Trust Terhadap Purchase Intention Bank Syariah di Jakarta (Studi Terhadap Masyarakat Muslim Kelompok Usia Muda di Jakarta) - Rahmantyo, Enrico Tri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Banks are financial institutions that play an important role in the economy. In Indonesia, there is Shariah Bank where all operations are based on Shariah principles. However, in Indonesia, there are still few young Muslims who use Shariah Bank for their economic needs. In this study, the researcher wants to determine the factors that influence young Muslims in Jakarta to use Shariah Bank products. The researcher used three variables in this study, namely Religiosity, Islamic Financial Literacy, and Trust. The research method used quantitative analysis with multiple linear regression. The results obtained in this study are that the Trust variable has a positive influence on the purchase intention of Shariah bank savings products. Meanwhile, the variables of Religiosity and Islamic Financial Literacy do not have a positive influence on the purchase intention of Shariah bank savings products.